Case Report: Anomalous drainage vein sampling for diagnosing aldosterone-producing lesions undetectable by segmental adrenal venous sampling in a two-case series - Tannai, Hiromitsu; Oguro, Sota; Kamada, Hiroki; Tezuka, Yuta; Ono, Yoshikiyo; Omata, Kei; Takase, Kei (Frontiers in Radiology, 2025)
Adrenal vein sampling (AVS) is the gold standard for subtyping primary aldosteronism (PA). However, through conventional AVS, unilateral PA may be misdiagnosed as bilateral PA. Compared with conventional AVS, segmental AVS with additional sampling in adrenal tributaries can detect aldosterone-producing adenomas (APAs) with higher sensitivity. Herein, we describe two cases wherein high aldosterone levels were not detected through initial segmental AVS but were identified in anomalous drainage veins during the second AVS session. In Case 1, computed tomography (CT) during left adrenal arteriovenography revealed a fine renal capsular vein connecting an adrenal nodule to the third lumbar vein. Sampling in this vein during the second AVS revealed high aldosterone levels. The surgical specimen showed the presence of an 11 mm APA. Furthermore, Case 2 presented with bilateral small adrenal nodules; bilateral renal capsular vein sampling was performed during the second AVS session. The samples from the renal capsular vein connected to the renal vein revealed considerably high aldosterone levels. Left adrenalectomy revealed the presence of a 6 mm aldosterone-producing nodule. These cases highlight the importance of anomalous drainage vein sampling, the limitation of conventional and segmental AVS in diagnosing PA, and the utility of CT during adrenal arteriovenography for estimating the drainage route.